Effect of an educational program based on cognitive behavioral techniques on fear of childbirth and the birth process - Tuba Uçar; Zehra Golbasi (Journal of Psychosomatic Obstetrics and Gynecology, 2019)
Objective: This study determined the effect of an educational program based on cognitive behavioral techniques (CBT) provided for pregnant women to address their fear of childbirth. Methods: This study was conducted experimentally using pretest–posttest and a control group. A total of 111 Turkish pregnant women were recruited with 52 in the intervention group and 59 in the control group. The intervention group attended the educational program on coping with childbirth fears based on CBT, which took 3 weeks over six sessions. The Wijma Delivery Expectancy/Experience Questionnaire, version-A (W-DEQ-A) was administered to both groups as the posttest. The researchers monitored the pregnant women’s labor and delivery and the State Anxiety Inventory (SAI), Numeric Pain Rating Scale (NPRS) and Birth Process Evaluation Form were completed. Results: The post-education W-DEQ-A score was 63.5 in the control group and 39.4 in the intervention group (p < .001). Their labor pain was lower, the second stage of labor was shorter and birth was more satisfactory for the intervention group than for the control group (p < .05). The CBT-based educational program and pain severity during childbirth were the significant predictors of satisfaction with childbirth (β = 0.354; β = –0.324, respectively; p < .05 for all). Conclusions: The CBT-based educational program on coping with childbirth fears reduced pregnant women's fear of childbirth and positively affected their birth experience.